The effect of surface water on the performance of PV module / Muhammad Haikal Kamaruddin - Kamaruddin, Muhammad Haikal (2013)
Lifespan of photovoltaic cells is estimated around 20-25 years. The rate of degradation will increase rapidly if the temperature goes beyond the certain limit The increase of working temperature of photovoltaic (PV) cell through absorption solar radiation is inversely proportional to the electrical efficiency. With the purpose of increase the PV efficiency, it is crucial to keep the PV cell temperature at minimum level. This paper introduces the probability of increasing the performance in terms of output power and efficiency using passes running water on the surface of PV module. Results gained from this method are compared with the unaltered PV module. The results show that it manage to bring down the operating temperature of PV module but the water itself interfere with the solar absorption and dropped the efficiency of the PV module. All the data was recorded using solar module analyzer (PROVA 200) and from the short circuit current of module shows that the electrical performance is worsen.